The electrochemical effects of pitch stabilization for supercapacitor-grade activated carbon precursors - Lee, Jeong Han; Ju, Min O.; Kang, Yong-Mook; Roh, Kwang Chul (Elsevier BV, 2024)
Petroleum pitch (PP) is a by-product generated during the petroleum refining process, characterized by its high carbon content, tunable structure, and cost-effectiveness. These attributes have spurred extensive research into its potential as a carbon material. In this study, we prepared both untreated PP and oxidative stabilized PP (sPP) to explore the influence of pitch structural modifications on physical and electrochemical properties following carbonization and activation. Stabilizing the pitch above its softening point introduced oxygen functional groups on the surface, reaching levels of up to 19.6 at.%. These structural changes concurrently reduced aromaticity while increasing the coking value. Two types of activated carbons suitable for supercapacitors were derived from these distinct pitches, and their energy storage capacities were correlated with precursor pitch structural properties. The sPP-derived activated carbon exhibited a remarkable gravimetric specific capacitance of 39.6 F g- 1 relatively lower specific surface area of 1122 m2 g-1. However, it demonstrated an increased electrode density and shallow ion intercalation within its graphitic structure, resulting in a notable volumetric capacitance of 26.0 F cc-1. This research not only sheds light on the electrochemical effects of pitch stabilization but also provides a foundation for the development of high-performance activated carbon materials through tailored modifications to the PP structure. , owing to its high specific surface area of 2508 m2 g-1. Conversely, PP-derived activated carbon exhibited a